Structural and Functional Determinants of Conserved Lipid Interaction Domains of Inward Rectifying Kir6.2 Channels - Cukras, Catherine A. (The Rockefeller University Press, 2002)
All members of the inward rectifiier K(+) (Kir) channel family are activated by phosphoinositides and other amphiphilic lipids. To further elucidate the mechanistic basis, we examined the membrane association of Kir6.2 fragments of K(ATP) channels, and the effects of site-directed mutations of these fragments and full-length Kir6.2 on membrane association and K(ATP) channel activity, respectively. GFP-tagged Kir6.2 COOH terminus and GFP-tagged pleckstrin homology domain from phospholipase C δ1 both associate with isolated membranes, and association of each is specifically reduced by muscarinic m1 receptor–mediated phospholipid depletion. Kir COOH termini are predicted to contain multiple β-strands and a conserved α-helix (residues ∼306–311 in Kir6.2). Systematic mutagenesis of D307-F315 reveals a critical role of E308, I309, W311 and F315, consistent with residues lying on one side of a α-helix. Together with systematic mutation of conserved charges, the results define critical determinants of a conserved domain that underlies phospholipid interaction in Kir channels.